Representing metadata constraints in Common Logic. (11th November 2009) - Delugach, Harry S.
This paper presents a standards-based approach to specifying and reasoning about metadata constraints based on existing metadata registry standards, existing terminologies and Common Logic. The paper introduces Common Logic's basic principles and theory, and applies it to several examples where we might want to reason about metadata constraints. It is our expectation that these additional constraints will be developed by the makers of the metadata for a given data source, and will be included in a metadata registry for exchange with any subscriber to the metadata.